Analysis the Quality of Hospital Information Systems and Work Coordination on the Performance of Health Workers at Waru Hospital, Pamekasan Regency - Abdul Rahman; Byba Melda Suhita (Universitas STRADA Indonesia, 2023)
Various hospitals that still survive using conventional administrative systems have shown many lost profit opportunities due to weak coordination between departments and lack of fast, precise, accurate and integrated information support. This of course will affect the quality of services provided to stakeholders, especially patients. The purpose of this study was to analyze the influence of the quality of hospital information systems and work coordination on the performance of health workers at Waru Hospital, Pamekasan Regency. The design of this study was a quantitative observational study with a cross-sectional approach with a research focus aimed at analyzing the influence of the quality of hospital information systems and work coordination on the performance of health workers at Waru General Hospital, Pamekasan Regency.